PENGARUH GAME KAHOOT TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV DI SEKOLAH DASAR - Elfi Indriani; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Students' interest in learning science is still relatively low, because not a few students consider science as a relatively difficult subject. Interest in learning is very important for a student's learning. The use of interesting and interactive learning media increases students' interest in learning science. The interactive media used in this study uses the kahoot game in learning. This study aims to determine the effect of kahoot games on students' learning interest in grade IV science learning in elementary schools. This research uses quantitative research methods with Quasi Experimental Design with Posttest Only Control Design. Sampling technique with non-probability sampling. This type of research tool uses a questionnaire containing 20 positive statements. In calculating the data analysis, this study used SPSS Statistics 26.0 to calculate the normality test, then the hypothesis was tested using the t-test at a significant level of 0.05. The results of the calculation of the t-test hypothesis test in both classes show ????ℎ???????????????????? > ???????????????????????? namely 2,462 > 2.011 which indicates that there is an influence of kahoot games on students' interest in learning science in class IV SD Negeri 20 Pahambatan Balingka.